Oppfinnelsen av Hugo Cabret en roman i ord og bilder - Selznick, Brian 1966- (Cappelen Damm, 2008)
When twelve-year-old Hugo, an orphan living and repairing clocks within the walls of a Paris train station in 1931, meets a mysterious toyseller and his goddaughter, Hugo's undercover life and his biggest secret are jeopardized